m(m+m)=-18

Simple and best practice solution for m(m+m)=-18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for m(m+m)=-18 equation:


Simplifying
m(m + m) = -18

Combine like terms: m + m = 2m
m(2m) = -18

Remove parenthesis around (2m)
m * 2m = -18

Reorder the terms for easier multiplication:
2m * m = -18

Multiply m * m
2m2 = -18

Solving
2m2 = -18

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Divide each side by '2'.
m2 = -9

Simplifying
m2 = -9

Reorder the terms:
9 + m2 = -9 + 9

Combine like terms: -9 + 9 = 0
9 + m2 = 0

The solution to this equation could not be determined.

See similar equations:

| 7x+14=24-5x | | -35=3(w-5)-5w | | -11+16(y+3)i=22x+32i | | 5w/4=20 | | .5-x-x=-1 | | 15x^3+8x^2-x=0 | | 5u-34=-8(u+1) | | 8x-8=62 | | 3x^2-12x=8-2x | | x(2x+-9)=45 | | -9/5-2/3u=-1/2 | | (X-2)=-1/4(x-8) | | 9x-3y=101 | | -2(x-4)+3(x+1)=17 | | 4n+4=34-2n | | 11g=66 | | N=-1.825 | | 6b+9h= | | (3x^2-6x-9)/(x-5) | | 2z/7-1=8 | | 28-4v=2v+4 | | -3x+17-5x=12-(6x+3) | | f(-49)=-5x+1 | | 3/4=7/x-9 | | 5x-2y+3x+y= | | -21=-9+4x | | 2x+10=5x+10-3x | | f(-2)=x^2-5 | | 8-2+a-9a= | | F(-2)=5x^2-7x+10 | | (4x+6)=(3x+9) | | (6-15)*(4+5)= |

Equations solver categories